Efeito do treinamento diafragmático na barreira antirrefluxo e nos sintomas de pacientes com esofagite de refluxo - Lima, Maria Josire Vitorino (2011)
The Gastroesophageal Reflux Disease (GERD) is a syndrome wicth one of the causes is a functional or anatomical change in the barrier mechanisms of gastric contents. It is a chronic disorder with a high and changeable estimated prevalence (from 10 to 50% of the population). Interventions in respiratory function, such as the use of CPAP (Continuous Positive Airway Pressure), can alter the occurrence of GERD, improving basal pressure and the rate of spontaneous relaxations of the Lower Esophageal Sphincter (LES). The main respiratory muscle is the diaphragm, whose crural part forms the anti-reflux barrier. The crural diaphragm is a skeletal muscle and hence it can be trained. Therefore, the main question is whether we could improve the anti-reflux barrier through physical therapy training of the diaphragm. OBJECTIVE: To show the training diaphragm may have significant effect on the antireflux barrier and symptoms in patients with reflux esophagitis. METHODS: Intervencional study it was measured the Baseline pressures (Bp) and the inspiratory pressures from the LES, both in mmHg. These measurements were done during the maneuvers of Respiratory Sinus Arrhythmia (RSA) and with inspiratory load (Threshold ® IMT) of 17 (Pth17), 35 (Pth35) and 70cmH2O (Pth70).We used a system of low-compliance perfusion manometry, and a sonde with a "dentsleeve" of 6cm. The diaphragmatic training was conducted during eight weeks with initial load of 30% of Maximal Inspiratory Pressure (MIP), with weekly increments of 5%. Each training session consisted of 10 series of 15 inspiratory incursions, with a pause from 30s to 60s between the series, and aberage of 30 minutes duration. RESULTS: Intervencion study with twelve patients carried GERD without hiatal hernia, of both genders (18-50 years old) The study has showed that the Bp increased significantly after the diaphragmatic training (19.7 ± 2.4 versus 28.5 ± 2.1, p = 0.0009, n = 12), as well as the RSA pressure (95,8±7,8 versus 122,5±12,7, p=0,0218). The LES pressure, during the maneuver with a resistive load of 17 cmH20, was higher after diaphragmatic training (117,3±12,8 versus 138,8±10,8, p=0,0308), white with a resistive load of 35 cmH20 it was similar (130,7±13,4 versus 138,8±10,8, p=0,5085). The LES pressure, during the maneuver with a resistive load of 70 cmH20, was higher after diaphragmatic training, although not statistically significant (127,3±14,0 versus 146,1±9,5, p=0,0909). The number of transient lower esophageal sphincter relaxations (tLESR), during one hour, decreased significantly after diaphragmatic training [20.00 (18.0 to 30.3) versus 13.5 (10.7 to 19.5), p = 0.0059)]. The scores of heartburn and regurgitation, based on the frequency of symptoms, were significantly lower after diaphragmatic training [3.0 (1.0 to 4.0) versus 0 (from 0.0 to 1.0), p = 0.0035] and [2.5 (0.0 to 4.0) versus 0 (from 0.0 to 4.0), p = 0.0084, respectively]. CONCLUSION: The diaphragmatic training improves the baseline pressure, decreases the tLESR and the symptoms of the GERD.